Effect of silica nanoparticles on the mechanical and physical properties of fibercement boards - Hincapié Rojas, Daniel Fernando; Pineda-Gómez, Posidia; Guapacha-Flores, John Fredy (Journal of Building Engineering, 2020)
The improvement of cement-based constructions and the preservation of natural resources has been a constant challenge for today's society. The use of nanomaterials is a new topic in cement industry to produce high performance concretes. In this work the effect of the addition of the silica nanoparticles, obtained from the rice husk, on the functional properties of fiber cement plates was studied. Three percentages of addition were evaluated in relation to the total amount of cement: 3, 5 and 7%. The changes in morphology, structure, thermal properties and flexural strength of fibercement boards as an effect of the incorporation of nanosilica were studied. The techniques of characterization of electron scanning microscopy, X-ray diffraction, thermogravimetry and mechanical tests were used. The evaluation of the morphology of the boards indicated that there is more formation of hydration products such as hydrated calcium silicate or tobermorite gel for the specimens manufactured with 5% addition. By means of structural analysis, the presence of important phases of hydration of the cement, such as portlandite and tobermorite, was corroborated. By means of the thermogravimetric analysis four characteristic stages of the decomposition of the fibercement were identified and it was also corroborated that increase the addition of nanoparticles generated a decrease in the amount of portlandite in the boards, which contributes with the resistance of the material. The mechanical analysis showed that there was an increase in resistance to bending resistance up to 16.25% for the board made with 5% addition of nanosilica compared to the sample without addition. These results allow inferring that due to its high pozzolanic reactivity, the nanoparticles promote the reaction with portlandite to form tobermorite, in favor of the strength of the fibercement boards. [Display omitted] •It is important to highlight the use of agricultural waste such as rice hush to obtain materials with added value such as nanosilica, through a process of incineration, leaching acidity and mechanical grinding of high energy; and in this way give an alternative use to these by-products and contribute to the preservation of natural resources.•This study allows us to contribute about the study of fiber-reinforced boards, since in the literature there is very little report of the effect of silica nanoparticles on this type of material.•With the development of this research it was possible to determine that the optimum percentage of addition of silica nanoparticles in the fiber cement is 5%. There is an improvement of functional properties of cement matrix.